Formulation and Evaluation of Lozenges from Durian Peel Extract (Durio zibethinus Murr) as an Antioxidant - Humairoh, Lia Intan; Alighiri, Dante (Journal of Science and Technology Research for Pharmacy, 2023)
The durian peel is known to possess antioxidant activity due to the presence of flavonoid compounds in it. However, the potential of durian peel as an antioxidant is yet to be fully utilized, necessitating innovative approaches. This research aimed to formulate durian peel extract into antioxidant lozenge tablets. The durian peel was extracted using the reflux method with 96% ethanol as the solvent. The lozenge tablets were prepared in three formulations with varying fillers, Formula 1 with mannitol, Formula 2 with combination of mannitol-lactose, and Formula 3 with lactose. Evaluation of granule quality and physical properties of the lozenge tablets showed that Formula 2, with 50% mannitol and 50% lactose concentration, had exhibited better granule quality and physical properties compared to the other formulations. It had a flow rate of 0,88 seconds, an angle of repose of 19,85°, a compressibility index of 10%, tablet friability of 0,33%, tablet hardness of 11,67 kg, and a disintegration time of 16 minutes. The antioxidant activity of the durian peel extract lozenge tablets was identified using the DPPH method, with vitamin C tablets and imboost lozenge tablets as positive controls. The sample of durian peel extract lozenge tablet demonstrated higher antioxidant activity (IC50 value = 197,25 µg/mL) compared to the imboost lozenge tablet (IC50 value = 268,09 µg/mL). However, the antioxidant activity was still inferior to that of the vitamin C tablet, which had an IC50 value of 86.81 µg/mL.